Checkpoint Inhibition in Microenvironment of Endometrial Cancer: The Emerging Role of KIR and NKG2A - Alameer, Zainab W. Abdulkhaleeq; Shani, Wafaa S. (Asian Pacific Journal of Cancer Biology, 2026)
The most common cancer of the female genital tract in developed nations is endometrial carcinoma (EC). Due in major part to population aging and the rising prevalence of diabetes and obesity, its incidence has grown by more than 132% globally over the last three decades. EC-related mortality has continued to rise even while improvements in early detection and treatment have raised survival rates. In contrast to other cancers like breast cancer, less is known about the immunological landscape of EC. Although T cell-based immunotherapies have revolutionized cancer treatment, certain tumor types and patient populations show limited responsiveness. As a result, the innate immune system in particular, natural killer (NK) cells has drawn more attention as a potential substitute effector in cancer immunotherapy. NK cells are powerful antitumor cytotoxic lymphocytes that are frequently compromised in the tumor microenvironment. These cells are controlled by a balance of activating and inhibitory receptors that recognize the lack of MHC class I molecules. Current treatment approaches block inhibitory receptors or stimulate activating ones in an effort to improve NK cells-mediated anticancer responses. With an emphasis on inhibitory receptors, including killer cell immunoglobulin-like receptors KIR and NKG2A, this review investigates the phenotypic and functional features of NK cells within the TME of EC. Understanding how modulation of KIR and NKG2A signaling can restore NK cells cytotoxicity provides a promising avenue for next-generation immunotherapies in EC.